Fat in the fire - British Broadcasting Corporation (London : BBC Enterprises, 1979)
The video is about the recent research suggests that special fat cells (Brown fat) may, ironically, help control weight by burning up surplus food. Could drugs therefore be found to stimulate brown fat cells and help overweight people lose their excess fat?
Backup available in VHS 1/2 in.
Keywords: Brown adipose tissue; Obesity -- Weight loss; Obesity